Lying Life: A New Concept towards Truth and Reality - Mario Tanga (Recent Trends in Arts and Social Studies Vol. 3, 2023)
The opposition between truth and lie is a question as old as Man. Indeed, it is as old as Life. The temptation has always been that of the bipolar opposition, which simplifies the field and offers absolutely certain references. So, we throw in the baby with the bathwater: to avoid possible ambiguities, we sacrifice any game of ambivalence or exchange. In this chapter, we will show chance, necessity and, sometimes, opportunity of an usually abhorred informational alteration and how fake/true are artificial, conventional categories. Information arises with life, and with information arises a gap between reality (or another information that is assumed as original and true) and information that represents, repeats or replaces it. This is a gap and it creates a difference, a duality, a not virtual distance, it opens a space for potential (or unavoidable?) un-faithfulness, incongruities, falsehood. Lie can be meant as alteration, as distortion, as denial, or as creation “ex nihilo” if referred to what (world reality or other informa-tion) is assumed as original and authentic. The ability to make and receive information logically entails that there cannot be and cannot be an absolute and entire coincidence between the information and its content and between the content and the referent. The deliberate divergence of the information source is added to the impossibility of this fact.